Study on Military Organization of Mughal Empire: Analyzing Akbar's Political Approach in Creating Mughal Union (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study is a historical study employing a qualitative approach methodology as a means of gathering and analyzing of data. The gathering of data was done through search of documents while the historical review, content analysis and source interpretation were used to analyze the data. This study found that Akbar has implemented several policies to unify the whole of the Indian subcontinent in order to achieve his mission of ‘Mughal Union’. However, some of his policies were controversial and drew from the Indian Muslims as the policies were deemed unacceptable and deviated from the true teachings of Islam. The opposition to his ideas did not however hinder him from achieving his political missions. This article, therefore, must be read as an exposition of a political figure’s efforts in his maneuver to consolidate his position. In addition to that, this article serves as an effort to analyze Akbar’s political approach which was deemed as attempts to proliferate Mughal political power through measures which ‘subdued’ Islam with the aim of creating unity of the people and hence creating ‘Mughal Union’.